ANÁLISE DOS TESTES DE CHAMA E HIDROSTÁTICO EM TUBULAÇÕES REFORÇADAS COM COMPÓSITOS PARA APLICAÇÃO NA INDÚSTRIA OFFSHORE - Marques Cruz, Jéssica de Brito; Limeira, Vanessa (Caderno de Graduação - Ciências Exatas e Tecnológicas - UNIT - ALAGOAS, 2019)
The increasing technological advance observed lately has required materials continuously refined by several sorts of industries. Conventional materials used in engineering have not been able to grant all this demand. In this scenario, the application of composite materials in the area of offshore petroleum exploration is constantly increasing. These materials show good mechanical properties, low weight and good resistance to corrosion, and for this reason, are applied in the pipes production that transport petroleum and other fluids from the ocean floor to the platform or ship. Accordingly, the present work aims to qualitatively analyze pipes reinforced with composite material for the application in the offshore industry. At first, pipes that suffered loss of thickness were reinforced with glass fiber composite material and subsequently subjected to fire and hydrostatic tests. The fire and hydrostatic tests were conducted according to ASTM F 1173 recommendation. As results, all the specimens passed the burn and hydrostatic tests, most of them fulfilling the requirement of A integrity and a pipe fulfilling B integrity - ASTM F 1173 [level L3 - IMO A 753 Resolution (18)].